2020
DOI: 10.1177/0391398820964483
|View full text |Cite|
|
Sign up to set email alerts
|

Selection of suitable pedicle screw for degenerated cortical and cancellous bone of human lumbar spine: A finite element study

Abstract: Pedicular arthrodesis is the traditional procedure in terms of increase in the biomechanical stability with higher fixation rate. The current work aims to identify the effect of three spinal pedicle screws considering cortical and cancellous degeneracy condition. Lumbar section L2-L3 is utilized and various load and moment conditions were applied to depict the various biomechanical parameters for selection of suitable screw. Three dimensional model is considered in finite element analysis to identify the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Several studies have reported approaches to improve the stability of pedicle screws, including enlarging the diameter of pedicle screws [ 20 ], modifying the screw thread [ 21 ], performing injectable pedicle screw [ 22 ], proper pedicle screw selection [ 23 ], fused lumbar spine [ 24 ], and directly injecting bone cement into the pilot hole [ 25 ]. A biomechanical study had proved that solid screws with retrograde cement pre-filling was capable of achieving improved initial fixation strength as compared to cannulated screws with cement injection via perforation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported approaches to improve the stability of pedicle screws, including enlarging the diameter of pedicle screws [ 20 ], modifying the screw thread [ 21 ], performing injectable pedicle screw [ 22 ], proper pedicle screw selection [ 23 ], fused lumbar spine [ 24 ], and directly injecting bone cement into the pilot hole [ 25 ]. A biomechanical study had proved that solid screws with retrograde cement pre-filling was capable of achieving improved initial fixation strength as compared to cannulated screws with cement injection via perforation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it can be concluded that a precise model of degenerated facet joints is essential for predicting future changes in facet joint loads following disc degeneration. FEM models have also been performed for the biomechanical investigation of various methods for managing multilevel myelopathy of the cervical spine [47][48][49][50][51]. For instance, in a recent study, an intact C2-C7 spine model was generated.…”
Section: Degenerative Disc Diseasementioning
confidence: 99%
“…21 Previous studies considering finite element analysis (FEA) have also suggested various instrumentation methods to achieve stability to degenerated segments. 22,23 Moreover, researchers have also proposed different stabilisation systems to replicate and simulate an actual spinal segment for better treatment solutions. [24][25][26][27][28][29] Accordingly, it is essential to study the range of motion and load study for any fixation device aiming for spinal stability.…”
Section: Introductionmentioning
confidence: 99%